2012
DOI: 10.1177/0333102411434808
|View full text |Cite
|
Sign up to set email alerts
|

Self-reported muscle pain in adolescents with migraine and tension-type headache

Abstract: Aim: To identify possible associations between muscular pain and headache in adolescents in a large population-based sample. Methods: Grammar school students were invited to fill in a questionnaire on headache and associated lifestyle factors. Headache was classified according to the German version of the International Classification of Headache Disorders (2nd edition). Muscular pain was assessed via denoting affected areas in schematic drawings of a body and via provoked muscular pain on controlled movements … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
79
0
9

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(91 citation statements)
references
References 34 publications
3
79
0
9
Order By: Relevance
“…The prevalence of headache in the studied population was 87.8%. Prevalence as high as this has been also reported by other authors 17,18 , however it is still possible to find lower figures (35.1%) 19 , and such differences may be explained by different methodological designs and by the ways to evaluate headache, since some studies classify as has having headache people presenting at least one headache episode in the last three months and other studies consider one episode in the last year. Recently, Albers et al 19 have proposed a systematic review on the prevalence of headache among children and adolescents and have concluded that its increase is proportional to age; however this finding is different from our study which has observed higher chance of reporting headache in the age group from 12 to 15 years of age as compared to adolescents from 16 to 19 years of age.…”
Section: Discussionmentioning
confidence: 56%
“…The prevalence of headache in the studied population was 87.8%. Prevalence as high as this has been also reported by other authors 17,18 , however it is still possible to find lower figures (35.1%) 19 , and such differences may be explained by different methodological designs and by the ways to evaluate headache, since some studies classify as has having headache people presenting at least one headache episode in the last three months and other studies consider one episode in the last year. Recently, Albers et al 19 have proposed a systematic review on the prevalence of headache among children and adolescents and have concluded that its increase is proportional to age; however this finding is different from our study which has observed higher chance of reporting headache in the age group from 12 to 15 years of age as compared to adolescents from 16 to 19 years of age.…”
Section: Discussionmentioning
confidence: 56%
“…The other accompanying factors are problem in sleep initiation, drooping of eyelids, diarrhea, feverishness, drowsiness, speech disturbance, swelling of ankles, tearing of eyes, aura, visual disturbances, transient loss of vision, periodic headache, vertigo, etc. Trigger factors could be identified in all patients; 81% patients had more than one identifiable trigger [1,2] factors, prominent were stress, poor sleep, environmental changes, head movements and mental stress, fasting, menstrual phase, emotional stress. Other less common identified factors were ocular strain, fasting, exertion, perfumes and journey.…”
Section: Observation and Resultsmentioning
confidence: 99%
“…None of them had any prophylactic medicines. Family history of migraine was seen in 30%, specially the females, [5,2] while a large proportion of patients (49%) did not feel the need for any consultation. Thirty percent of patients attributed their headache to stress, while only a small proportion (10%) attributed it to migraine.…”
Section: Observation and Resultsmentioning
confidence: 99%
“…Gabmann et al (2009) reported that 2.6% of 8-year-old and 10.7% of 15-year-old children had at least one headache weekly [20]. Other studies conducted in Canada, Southern England and Italy also show the same trends [21][22][23]. It has shown that body weight and sleep time are related to certain type, but not all of primary headache.…”
Section: Discussionmentioning
confidence: 98%